A palladium/Et3N·HI-catalyzed highly selective 7-endo alkyl-Heck-type reaction of epoxides and a DFT study on the mechanism. Issue 21 (7th September 2021) - Dong, Xu; Xu, Li-Ping; Yang, Yi; Liu, Yunxia; Li, Xin; Liu, Qing; Zheng, Liang; Wang, Fagang; Liu, Hui
Abstract : A highly efficient 7- endo alkyl-Heck reaction was achieved via palladium catalyzed ring-opening of epoxides, providing a variety of 6-aryl-2, 3, 4, 7-tetrahydro-1 H -azepin-3-ols and 6-aryl-2, 3, 4, 5-tetrahydrooxepin-3-ols. Abstract : A highly efficient 7- endo alkyl-Heck reaction was achieved via palladium catalyzed ring-opening of epoxides, providing a variety of 6-aryl-2, 3, 4, 7-tetrahydro-1 H -azepin-3-ols and 6-aryl-2, 3, 4, 5-tetrahydrooxepin-3-ols. Pd(PPh3 )4, a catalytic amount of Et3 N·HI and an additional ligand L4 are essential for this transformation. The methodology showed a broad substrate scope with excellent 7- endo selectivity. Preliminary mechanistic investigations provide evidence for the generation of alkyl radicals, indicating a hybrid palladium-radical process. DFT studies revealed that the C–C bond formation process proceeds through a rate-limiting concerted "epoxy ring opening and C–C coupling" step, which leads to a diradical species as a key resting state. A plausible mechanism initiated by an in situ generated HPd(ii )I species is proposed based on the preliminary exploration by experiments and DFT calculations.